North Africa From Ibn Sabah Al-Shatibi’s Journey - Sharmen Kreem Abdulrahman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This research, under the title North Africa from Ibn Sabah Al-Shatibi’s Journey, made it clear that the traveler Ibn Sabah made his journey in the eighth century AH / fourteenth century AD, to the eastern regions, especially to the areas subject to Islamic rule, when Andalusia was under Christian rule, and it was His goal in this trip is the Hijaz, for the purpose of Hajj, and from here the trip had another name, which is the Hijaz trip, and accordingly the research came in two sections: the first topic, the life of Ibn Sabah Al-Shatibi and his methodology in writing his trip, and the second topic describing North Africa from his trip and the civilized face of its regions From the civilizational construction such as a mosque and schools, mental and religious sciences, as well as scientific and economic life, especially agriculture, industry, trade and others, which was filled with the vocabulary of the trip when he passed through North Africa.